2012
DOI: 10.2165/11636260-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Lacosamide in the Concomitant Treatment of 130 Patients Under 16 Years of Age with Refractory Epilepsy

Abstract: BackgroundThe safety and effectiveness of lacosamide, an antiepileptic drug (AED) that selectively enhances the slow inactivation of voltage-gated sodium channels without affecting rapid inactivation, has been demonstrated in randomized, double-blind, placebo-controlled trials in adults with focal epileptic seizures. Although lacosamide is approved for use in patients over 16 years of age, limited clinical experience exists for younger patients.ObjectiveTo assess the efficacy and tolerability of lacosamide in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 17 publications
(28 reference statements)
1
7
0
3
Order By: Relevance
“…The use of lacosamide in patients younger than 17 years with partial-onset epilepsy has been studied both retrospectively and prospectively in several centers and has had favorable results (Table 1). 6,7,10 15 Lacosamide has also been used effectively in children with refractory status epilepticus as demonstrated by multicenter studies performed in Italy. 16,17 However the efficacy of lacosamide in generalized epilepsy both in adults and children appears to be less clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of lacosamide in patients younger than 17 years with partial-onset epilepsy has been studied both retrospectively and prospectively in several centers and has had favorable results (Table 1). 6,7,10 15 Lacosamide has also been used effectively in children with refractory status epilepticus as demonstrated by multicenter studies performed in Italy. 16,17 However the efficacy of lacosamide in generalized epilepsy both in adults and children appears to be less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Casas-Fernandez et al 10 published 2 patients with Lennox–Gastaut syndrome who had a ≥50% reduction in focal seizure frequency with the addition of lacosamide. Two of the 4 patients with Lennox–Gastaut syndrome studied by Rastogi and Ng 20 had a greater than 90% reduction in seizure frequency, while the frequency in the other 2 patients was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Lakozamid, Acetamido-N-benzyl-3-methoxypropionamide yapısında bir aminoasit olup etkisini voltaj-kapılı sodyum kanallarının yavaş inaktivasyonunu selektif olarak artırarak gösterir ve nöronların fizyolojik aktivitesinde değişiklik yapmadan patolojik hipereksitabilitesini azaltır. [6][7][8][9] Lineer farmakokinetik özelliği ile %100 oral biyoyararlanıma sahip, proteinlere düşük oranda bağlanan (<%15) fonksiyonelleştirilmiş bir aminoasit bileşimidir. Yarı ömrü 13 saat olup bir-iki saat içerisinde pik kan konsantrasyonuna ulaşır.…”
Section: Introductionunclassified
“…Lacosamide is a newer antiepileptic drug composed of the functionalised amino-acid acetamido-N-benzyl-3-methoxypropionamide, which was approved for adjunctive therapy for partial onset seizures in epilepsy patients over 16 years of age 1 2 Lacosamide has been demonstrated to achieve its antiepileptic effect by selectively enhancing slow inactivation of voltage-gated sodium channels and interfering with collapsin-response mediator protein 2, reducing the number of sodium channels that can be recruited for subsequent action potentials.…”
mentioning
confidence: 99%
“…Early studies have shown that lacosamide has a favourable side effect profile with side effects including dyspepsia, dizziness, headache, nausea, and vomiting 1 2 Cardiac effects are rare but have been documented in larger phase II trials as well as individual case reports and include atrioventricular block, atrial flutter/atrial fibrillation, and sinus node dysfunction 5 …”
mentioning
confidence: 99%